Validation of a maternal questionnaire on correlates of physical activity in preschool children. - McMinn, A; van Sluijs, E; Harvey, N; Cooper, C; Inskip, H; Godfrey, K; Griffin, S (2009)
BACKGROUND: Valid measures of physical activity correlates in preschool children are lacking. This study aimed to assess the validity, factor structure and internal consistency of a maternal questionnaire on potential correlates of four-year-old children's physical activity. METHODS: The questionnaire was designed to measure the following constructs: child personal factors; parental support and self-efficacy for providing support; parental rules and restrictions; maternal attitudes and perceptions; maternal behaviour; barriers to physical activity; and the home and local environments. Two separate studies were conducted. Study I included 24 mothers of four-year-old children who completed the questionnaire then participated in a telephone interview covering similar items to the questionnaire. To assess validity, the agreement between interview and questionnaire responses was assessed using Cohen's kappa and percentage agreement. Study II involved 398 mothers of four-year-old children participating in the Southampton Women's Survey. In this study, principal components analysis was used to explore the factor structure of the questionnaire to aid future analyses with these data. The internal consistency of the factors identified was assessed using Cronbach's alpha. RESULTS: Kappa scores showed 30% of items to have moderate agreement or above, 23% to have fair agreement and 47% to have slight or poor agreement. However, 89% of items had fair agreement as assessed by percentage agreement (>/= 66%). Limited variation in responses to variables is likely to have contributed to some of the low kappa values. Six questions had a low kappa and low percentage agreement (defined as poor validity); these included questions from the child personal factors, maternal self-efficacy, rules and restrictions, and local environment domains. The principal components analysis identified eleven factors and found several variables to stand alone. Eight of the composite factors identified had acceptable internal consistency (alpha >/= 0.60) and three fell just short of achieving this (0.60 > alpha > 0.50). CONCLUSION: Overall, this maternal questionnaire had reasonable validity and internal consistency for assessing potential correlates of physical activity in young children. With minor revision, this could be a useful tool for future research in this area. This, in turn, will aid the development of interventions to promote physical activity in this age group.